Risco para úlcera por pressão em idosos institucionalizados - Cristiane Rabelo Lisboa (2010)
Pressure ulcer (PU), an important health problem in the institutionalized elderly population,does not only increase spending on care delivery, but also entails important repercussionsfor their lives, such as increased morbidity and decreased quality of life, and may even leadto death. This descriptive cross-sectional correlation study aimed to analyze the risk factorsfor the development of PU among institutionalized elderly. Participants were 97 elderly, aged60 years or older, who lived at two homes for the aged (HA) in an interior city in MinasGerais, Brazil. For data collection, the following were used: instruments to identify the elderly,with sociodemographic variables and clinical conditions; Braden Scale; Katz Scale;Subjective Global Nutritional Assessment and serum albumin level assessment, applied bythe researcher and three trained nurses. The collected data were submitted to descriptiveand inferential analysis, using Kolmogorov-Smirnov, Students t, Pearsons chi-square,Fishers Exact and Mann Whitneys Test. The researcher looked for associations betweenfunctional disability, nutritional status and risk for the development of PU, so as to establishthe risk prediction. To assess the factors that contributed to the occurrence of PU, the logisticregression model was used, with PU occurrence as the response variable. Most elderly werewomen (59%), with 77 years as the mean age, illiterate (55%), white (67%), single (63%),without children (68%) and coming from their own home (49%). Before beinginstitutionalized, 30% lived alone and faced difficulties to perform activities of daily living(ADLs), which was the main reason for the institutionalization. Cardiovascular diseasespredominated (72%), as well as the use of neuroleptics or psychotropics (80.4%) andantihypertensives (57.7%). Arterial hypertension and diabetes were present in 62% and 20%of the elderly, respectively. The mean score on the Braden scale was 19.24 points, and 36%of the elderly presented risk for the development of PU. Among the elderly, 77% weresomewhat independent for ADLs, all were classified as well nourished and the majority(88%) had normal serum albumin levels. It was observed that 10.3% had PU, frequentlylocated in the sacral (45%) and trochanter (19%) region. Stage IV (37%) and III (24%) PUpredominated. No statistically significant difference (p>0.05) was found between people withor without PU in terms of clinical variables, medication use and with regard tosociodemographic variables, except for instruction level. Statistically significant differenceswere found for variables related to ADLs and Braden subscales (p<0.05) and in the presenceof normal serum albumin levels (p<0.002), besides mild depletion (p<0.009). High correlationwas found between the Katz Scale Categories and the Braden Scale Score (correlationcoefficient = 0.839; p<0.05) and low correlation between Bradens nutrition subscale andserum albumin level (correlation coefficient = 0.277; p<0.05). A statistically significant relationwas found between serum albumin level, Braden Scale Score and existence of PU. Thisresearch contributes to knowledge on risk factors for PU in institutionalized elderly, butfurther studies are needed to verify the relation between clinical and psychosocial conditionsand PU development.